2019
DOI: 10.28945/4375
|View full text |Cite
|
Sign up to set email alerts
|

Grit and Persistence: Findings from a Longitudinal Study of Student Performance

Abstract: Aim/Purpose: The purpose of this study was to examine whether grit was a contributing factor to student persistence and success at minority serving institutions. Background: A number of studies conducted in the past fifteen years have concluded that grit is a positive predictor of achievement across many domains. But, is grit really the ultimate panacea for student success? This longitudinal study sought to answer that question by specifically focusing on business students attending a mid-Atlantic minority-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Online teaching is different because the instructor is not there to make students vigilant. The e‐learning system makes the role of the teacher more complex, as teachers have to collect, prepare, and present the information via the internet as a course facilitator (Adedoyin & Soykan, 2020 ; Bdair, 2021 ; Buzzetto‐Hollywood, 2007 ). The complexity of online teaching has increased the workload of teachers many folds (Adnan & Anwar, 2020 ; Connolly & Begg, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Online teaching is different because the instructor is not there to make students vigilant. The e‐learning system makes the role of the teacher more complex, as teachers have to collect, prepare, and present the information via the internet as a course facilitator (Adedoyin & Soykan, 2020 ; Bdair, 2021 ; Buzzetto‐Hollywood, 2007 ). The complexity of online teaching has increased the workload of teachers many folds (Adnan & Anwar, 2020 ; Connolly & Begg, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…As explained in the literature review, grit and mindset go hand in hand (Burgoyne, et al, 2018) and grit can be a predictor of success (Buzzetto-Hollywood & Mitchell, 2019). As such, this intervention introduces grit early.…”
Section: Gritmentioning
confidence: 94%
“…Many studies have reported that grit can serve as a predictor of success (Buzzetto-Hollywood & Mitchell, 2019). For example, Eskreis-Winkler, Duckworth, Shulman, and Beal (2014) examined high school juniors in 98 Chicago Public Schools who completed the 12-item grit assessment.…”
Section: Gritmentioning
confidence: 99%
See 2 more Smart Citations